Penerapan Pedoman Umum Gizi Seimbang dalam Pemeliharaan Kesehatan Jantung pada Ibu Peserta dan Bukan Peserta Klub Jantung Sehat di Kalurahan Pleret Bantul Yogyakarta - Rizqie Auliana, Hainur Fardatin (Berita Kedokteran Masyarakat (BKM), 2008)
Background:  This  study  aims  to  see  1)  knowledge  concerning  nutrition  2)  knowledge  concerning  heart sickness  and  applying 13 message of  base  in  everyday  life mothers’  participant  of active  healthy heart  club which have  done effort  operation of  heart sickness  risk.Method: Research  type  is survey with  location  research  of Kalurahan Pleret District of Pleret Sub-Province  of Bantul  Yogyakarta. Population  Research  is  homogen with  housewife  criterion  have  age  20-55  year  with consideration of  risk  factor  at woman  happened age  55  year  so  that  before age  are  they  have prepared  herself healthy  life. Research Sample  selected by  simple sampling  random counted  30 housewife  people participant  of active healthy heart club  ( gymnastic group) and 30 housewife people  is not participant of healthy heart club  (not gymnastic group). Research data collected use 3  instruments  that are knowledge  test of nutrition,  test knowledge of  heart sickness  and  questioner  applying  13 messages  of  PUGS. Validity  and  reliability  instrument as  data collectors with  correlation  product moment  test  and  kruder-richardson  technique.Result and  conclusion: Result of  research show  1)  knowledge  of nutrition  between gymnastic  group and  not gymnastic group have difference 0,6.  In gymnastic group 29 people  is good and   not gymnastic group 27 people is good, with mean  assess  gymnastic  group 14,97  and not  gymnastic group   14,37, meaning most  researches sampel  have  owned  knowledge  of  good  gizi,  2)  knowledge  concerning  heart  sickness  between group  have difference  0,27,  all  sample have  good  knowledge  of heart  sickness with mean assess  gymnastic  group  13,75 and  not  gymnastic  group 13,1,  and  3)  all sampel  have  good  applied  13 message  of  base  of  PUGS better  in everyday  life,  this matter  for  gymnastic  group have  as according  to behavioral  theory  that  good  knowledge  is basis  for  behavior.Keywords  : PUGS, heart disease, SJS